1995
DOI: 10.1111/j.1600-0536.1995.tb00507.x
|View full text |Cite
|
Sign up to set email alerts
|

2‐methoxy‐6‐pentyl‐1,4‐dihydroxybenzene (miconidin) from Primula obconica: a possible allergen?

Abstract: Miconidin (2-methoxy-6-pentyl-1,4-dihydroxybenzene) and the allergen primin (2-methoxy-6-pentyl-1,4-benzoquinone) have been isolated from fresh unchopped plant material (leaves, stems and flowers together) of Primula obconica. Miconidin and primin were obtained in approximately equal amounts and their structures determined by NMR and GC-MS. Miconidin, which is biogenetically related to primin, has not previously been isolated from Primula species, and the possibility that miconidin is an allergen in P. obconic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…However, the horticultural uses of P. obconica have been limited due to the allergic compounds i.e., primin (a homologue of benzoquinones) and miconidin (a homologue of dihydroxybenzenes), in many cultivars Marner, 1995, 1996;Krebs and Christensen, 1995;Christensen and Larsen, 2000). In a number of sensitization experiments 2-methoxy-6-alkyl-1,4-benxoquinones with branch side chain length C1-C15, including primin, have showed an increase of the sensitizing capacity with increasing length of the alkyl side chain from C-1 to C-13 (reaching maximum activity at an alkyl chain of 10 to 11 carbons), but the sensitizing potency decreased beyond 13 carbons and the sensitization hardly occurred at C-1 to C-3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the horticultural uses of P. obconica have been limited due to the allergic compounds i.e., primin (a homologue of benzoquinones) and miconidin (a homologue of dihydroxybenzenes), in many cultivars Marner, 1995, 1996;Krebs and Christensen, 1995;Christensen and Larsen, 2000). In a number of sensitization experiments 2-methoxy-6-alkyl-1,4-benxoquinones with branch side chain length C1-C15, including primin, have showed an increase of the sensitizing capacity with increasing length of the alkyl side chain from C-1 to C-13 (reaching maximum activity at an alkyl chain of 10 to 11 carbons), but the sensitizing potency decreased beyond 13 carbons and the sensitization hardly occurred at C-1 to C-3.…”
Section: Resultsmentioning
confidence: 99%
“…Since 1888, however, P. obconica has been reported as a significant cause of allergic contact dermatitis, particularly in Europe (White, 1888;Rook, 1965;Aplin and Lovell, 2001). Therefore, the chemical composition of volatile oil of this poisonous plant has attracted phytochemists' attention, and two allergic compounds, i.e., miconidin (2-methoxy-6-penty-1,4-dihydroxybenzene) and primin (2-methoxy-6-pentyl-1,4-benzoquinone), have been isolated from the volatile oil of leaves, stems and flowers (including pedicel and calyx) of some European cultivars (Malect et al, 1992;Krebs and Christensen, 1995;Christensen and Larsen, 2000). The presence of allergic compounds has dramatically limited world wide commercial cultivation of P. obconica, even other ornamental primroses.…”
Section: Introductionmentioning
confidence: 99%
“…22) generally affects the eyelids, face, neck, fingers, hands, and forearms, but P. obconica can also cause conjunctivitis and erythema-multiforme-like eruption [272]. The most important allergen of Primula is a quinone named primin [273], formed by oxidation of its biosynthetic precursor miconidin (which is also allergenic [274]) in minute glandular hairs (trichomes) present at the surface of the plant (Fig. 23).…”
Section: Primulaceae (Primrose Family)mentioning
confidence: 97%
“…In a relative species like the poison primrose (Primula obconica) native to China, the allergenic principle is an alkylbenzoquinone, better known as primin, which accumulates under the cuticle of the trichomes that cover the leaves (Fernández de Corrés et al, 1987). It was demonstrated that the 1,4 diphenol corresponding to primin, namely miconidin, occurs in the intact fresh plant in equal quantity (Krebs and Christensen, 1995).…”
Section: Relationship Between the Medicinal Plants Used And Their Conmentioning
confidence: 99%